Analysis of Medicolegal Deaths in Sandeman Civil Hospital Quetta, Balochistan - MARIAM ARIF , MUHAMMAD MAQSOOD, MURAD ZAFAR MARRI, M. ZAHID BAHIR (Journal of Fatima Jinnah Medical University, 2018)
A retrospective study was done on the cases brought for postmortem examination in the medicolegal section of Sandeman Civil Hospital Quetta during 2009. It is a teaching Hospital of Bolan Medical College Quetta. All the cases from Quetta city, suburbs and rural area were included in the study and results were analyzed. Objectives: The aim of the study was to know manners of death and modalities in medicolegal deaths presented in medicolegal section of Sandeman Civil Hospital Quetta Balochistan. Study Design: Retrospective study. Place and Duration of Study: This study was conducted from 1st January, 2009 to 31st December, 2009 in Medicolegal section Casualty Department at Sandeman Civil Hospital Quetta, a teaching Hospital of Bolan Medical College, Quetta. Subjects and Methods: Materials for this study have been collected from Sandeman Civil Hospital Quetta Casualty Medicolegal Section including police reports, postmortem reports and clinical notes. During one year study period, a total of 329 medicolegal deaths were presented for postmortem examination in Civil Hospital, Quetta. Males (91.49%) were more commonly involved as compared to females (8.51%). All these cases were grouped according to age and gender, manners and modalities of medicolegal deaths (unnatural). The data thus collected is analyzed on Microsoft program. We have taken permission from Police Surgeon Sandeman Civil Hospital Quetta for entire study Results: Most common manner of death was homicide followed by accident, suicide, natural and undetermined in overall age groups. Firearms were the predominant weapons of infliction (70.78%) and the intent was mostly homicidal (77.52%). Among accidental deaths, a total of 47 (43.93%) persons lost their lives in Road Traffic Accidents. Males constitute (91.49%) and females (8.51%) of all the medicolegal deaths The age group most commonly involved was 20-29 years (50.56%) followed by 30-39 years (21.60%). Percentage of urban resident victims was high as compared to rural populace. Conclusion: This study concludes that Homicide was the most dominant manner of death among the unnatural deaths. Firearms deaths were commonest form of homicide, RTA was the commonest in the accidental deaths. Suicide was the rarest manner of death.